Republic of Madagascar : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2004)
This paper examines the first annual report on the implementation of Madagascar's Poverty Reduction Strategy Paper (PRSP). The report reviews the status of achievements on policy measures, action plans, as well as reforms concerning the Initiative for the Heavily Indebted Poor Countries (HIPC). It covers the first year of PRSP implementation corresponding to the period from July 2003 to June 2004. It also highlights the connections between the achievements and objectives, programs, and indicators.